PERSONALITY FEATURES OF THE PERSONS WITH CORRUPTIVE BEHAVIOR - L. M. Zakirova (Russian Journal of Economics and Law)
The article is devoted to one of the most complex and multi-sided aspects of the modern personality psychology – corruptive behavior. The article presents the personality features of persons apt for corruptive behavior, that is, the level of subjective control.